Designing modules of system dynamics in decision support systems - A. B. Sorokin; L. M. Zheleznyak; D. V. Suprunenko; V. V. Kholmogorov (Российский технологический журнал)
Objectives. When creating models of system dynamics, the basic construct at the design stage is the representation of the process under study in terms of a causal relationship consisting of a positive feedback loop and a negative feedback loop. The construction of a model of a dynamic environment can experience a number of difficulties in using feedback. This work shows the possibility of designing modules of system dynamics for decision-making systems based on the situational-activity approach. The study proposes the gap in knowledge about models of system dynamics to be filled with a conceptual model of an act of activity, by means of which an expert system can be implemented based on production rules. In this context, conceptual models are applied to human reasoning with reference to certain types of activity. The objective of the study was to investigate the possibility of applying the situational-active approach to designing models of system dynamics of infectious diseases based on particular representations of the conceptual structure of the act of activity.Methods. By synthesizing Bolotova's situational algorithm and Shchedrovitskiy's system-activity approach, the conceptual structure of the act of activity is presented as a methodology of the situational-activity approach. The analysis of this structure leads to the construction of a plan of processual structure and a plan of analytical relationships. The article proposed a hypothesis that the process representations describe the notation of flows and levels, and the analytical relationships implement differential equations. In order to prove this hypothesis, the subject area of infectious diseases was investigated.Results. Based on the set of these plans, a graphic image was synthesized for constructing models of system dynamics, which is identical to the diagram of flows and levels of development of the SIR process. However, the problem of constructing conceptual structures is nontrivial, complex, and laborious. Therefore, the Designer-Solver-Interpreter software suite was implemented. The software tools enable a visualization of the conceptual structures and implementation of the knowledge bases for expert models of system dynamics. It also tests the completeness and viability of the model.Conclusions. To date, there is no single conceptual structure for designing expert systems and situational and simulation dynamic models. The proposed method and software tools allow these problems to be resolved using the situational-activity method. Various types of dynamics in expert systems interact, thus confirming the reliability of knowledge in the models of system dynamics. The conceptual structures of the act of activity are the core part of designing expert systems, while he derivative process and analytical representations of the act of activity are the core part of developing modules of system dynamics.